2004
DOI: 10.1515/cclm.2004.049
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nucleosome, anti-chromatin, anti-dsDNA and anti-histone antibody reactivity in systemic lupus erythematosus

Abstract: Anti-nucleosome (anti-chromatin) antibodies play a key role in the pathogenesis of systemic lupus erythematosus (SLE). The objective of the present study was to determine the clinical significance of anti-nucleosome (anti-chromatin) antibodies, anti-dsDNA antibodies and anti-histone antibodies in patients with SLE in relation to patients with positive nuclear antibodies and healthy controls. We measured anti-nucleosome (anti-chromatin) antibodies, anti-dsDNA antibodies and anti-histone antibodies in 70 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
1
17
0
8
Order By: Relevance
“…Although anti-NCS Ab have been detected both in active and inactive SLEs [12,24], a close relationship between anti-NCS Ab and SLE disease activity evaluated by SLEDAI score [15,23,24,35] or the European Community Lupus Activity Measure (ECLAM) score [16,30] has been summarized. Benucci et al [16], also demonstrated the significantly lower levels of C3 and C4 in patients with positive anti-NCS Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Although anti-NCS Ab have been detected both in active and inactive SLEs [12,24], a close relationship between anti-NCS Ab and SLE disease activity evaluated by SLEDAI score [15,23,24,35] or the European Community Lupus Activity Measure (ECLAM) score [16,30] has been summarized. Benucci et al [16], also demonstrated the significantly lower levels of C3 and C4 in patients with positive anti-NCS Ab.…”
Section: Discussionmentioning
confidence: 99%
“…LES, LES induzido por drogas, artrite juvenil idiopática, síndrome de Felty, esclerose sistêmica, CBP, hepatite auto-imune (18) Homogêneo DNA nativo LES, LES induzido por drogas, artrite juvenil idiopática, síndrome de Felty, esclerose sistêmica, cirrose biliar primária, hepatite auto-imune…”
Section: Dna Nativounclassified
“…The sensitivity of the various tests for the different autoantibodies against chromatin components was relatively low (11%-40%) when compared to the literature data on adult SLE. 11,[36][37][38][39][40][41][42][43][44][45] This may be related to specifi c features of JSLE and to the ethnic makeup of the studied sample or to the fact that most JSLE patients were under immunosuppressive therapy at the moment of serum harvest. In the present study 22 of 23 (96%) anti-dsDNA ELISA positive samples were also anti-CHR-20 positive.…”
Section: Discussionmentioning
confidence: 99%